Face to face with political Islam - BURGAT, Francois (I B Tauris Pub., 2003)
The portrayal of Islamic movements as a tide of religious fanaticism threatening the West, and major participants in the coming "clash of civilizations", has provoked a multifaceted debate of great significance to the future of international relations. This text argues that political Islam's desire to restore a culture distorted by colonization does not necessarily compromise its progress to more democracy and greater tolerance. From Rabat to Gaza, through Algiers and Cairo, the author carried out his enquiry through interviews with prominent Islamists, and he allows them to speak for themselves in the book. Among the issues addressed are the relationship between Islam and modernity, Islamism and women, and questions of violence.